2008
DOI: 10.1002/glia.20654
|View full text |Cite
|
Sign up to set email alerts
|

Identification of midbrain floor plate radial glia‐like cells as dopaminergic progenitors

Abstract: The floor plate (FP), a signaling center and a structure rich in radial glia-like cells, has been traditionally thought to be devoid of neurons and neuronal progenitors. However, in the midbrain, the FP contains neurons of the dopaminergic (DA) lineage that require contact with radial glia-like cells for their induction. We, therefore, decided to explore the interaction relationship between radial glia and neurons during DA neurogenesis. Taking advantage of a novel FP radial glia-like cell culture system and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 47 publications
7
89
0
1
Order By: Relevance
“…Fate mapping experiments have indicated that mDA neurons originate from progenitors sorted for the FP marker CORIN (Ono et al, 2007) or expressing the radial glia marker Glast/Slc1a (glial high affinity glutamate transporter) (Bonilla et al, 2008). This shows that mFP radial glial cells, unlike FP radial glia in other brain regions, can undergo neurogenesis and are mDA progenitors.…”
Section: Specification Of Mda Progenitors and Suppression Of Lateral mentioning
confidence: 99%
“…Fate mapping experiments have indicated that mDA neurons originate from progenitors sorted for the FP marker CORIN (Ono et al, 2007) or expressing the radial glia marker Glast/Slc1a (glial high affinity glutamate transporter) (Bonilla et al, 2008). This shows that mFP radial glial cells, unlike FP radial glia in other brain regions, can undergo neurogenesis and are mDA progenitors.…”
Section: Specification Of Mda Progenitors and Suppression Of Lateral mentioning
confidence: 99%
“…1 and 2) must activate genes required for the development of a correct A9-DA phenotype, at a time in the mouse when the cells exit the cell cycle [21,22]. Nurrl expression in the mouse (cooperating with Pitx3) is critical for the acquisition of the correct DA phenotype (that requires co-expression of TH, AADC, VMAT2 and DAT) [17,22,73,74].…”
Section: Activation Of Developmental Pro-dopaminergic Genesmentioning
confidence: 99%
“…VM DAn originate from precursors residing in the mesencephalic floor plate (FP), both in rodents and humans, which show features of radial glia [9][10][11][12], reviewed by [6,[13][14][15][16][17][18][19][20][21][22][23][24]. In spite of the importance of identifying a well-characterized and reliable source of human A9-DAn, the present situation is that all neural stem/precursor cultures explored so far present numerous limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of success in generating functional DA neurons of a mesencepahlic identity was explained when it was revealed that mesDA neurons have their cellular origin from the midbrain floor plate rather than from the neuroepithelium and that the floor plate transcription factor FOXA2 is an important gene necessary for correct mesDA specification and maintenance [16][17][18][19]. In rodents and humans, The enzyme tyrosine hydroxylase (TH) is a required enzyme for DA synthesis, and is often used as a key marker of DA neurons.…”
Section: Building Mesda Progenitors Through Developmental Pathwaysmentioning
confidence: 99%